MODEL PEMBELAJARAN EXPERIENTIAL KOLB DENGAN VISUALISASI VIRTUAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATA KULIAH FISIKA DASAR LISTRIK (STUDI KASUS: TEKNIK INFORMATIKA UNIVERSITAS MAJALENGKA) - Tantri Wahyuni (Jurusan Teknik Informatika, 2015)
Based on the results of a case study that researchers do at one Colleges in Majalengka, obtained test student understanding of concepts in basic physics course with an average rating of 5.5. Thus it can be said that the students understanding of the concept is still relatively low. This is because the lecturers teaching model applied. The learning model used is the conventional learning models, so that students tend to be passive. Consequently, understanding the concept of low student. For that, we need appropriate learning models. Kolb experiential model of the virtual visualization of one of the appropriate alternative, because the students are actively and creatively build knowledge. The purpose of this study was to determine an improved understanding of the concept after application of Kolb's model of experiential virtual visualization. The study design pretest-posttest control group design, engineering informatics IIA, half as experiental class.